Upper Lower Segment Ratio Comparison between Obese and Normal Children Aged 7 to 10 Years Old - Azhar, Muhammad Zulfikar; Fadil, R.M. Ryadi; Sahiratmadja, Edhyana K. (Althea Medical Journal, 2016)
Background: Upper lower segment ratio is an anthropometric measurement that often used to detect the presence of abnormal growth. Growth is affected by many factor, one of them is nutrional status. Obesity prevalence in Indonesian children increases annually. These children show an accelerated growth in pre-puberty compared to normal children in their age. This study aimed to analyze the difference in upper lower segment ratio between obese and normal children aged 7 to 10 years old.Methods: A cross sectional study was carried out in children aged 7 to 10 years old in three Elemantary School in Bandung during SeptemberâOctober 2013. Height and weight were measured to calculate body mass index (BMI) score and were grouped into obese (BMI >95th percentile) and normal (BMI 10thâ85th percentile). The upper lower segment ratio was compared between obese and normal children and the level of the significant difference were analyzed by unpaired T-test.Results: From a total of 200 children recruited, 90 were obese and 110 were normal. There was no significant difference between upper lower segment ratio in obese and normal children (p=0.603) with mean ratio 1.137 and 1.142 respectively. The mean of upper lower segment ratio in obese boys was higher than normal boys (mean ratio 1.15 and 1.14 respectively), but obese girls had a lower ratio compared to normal girls (mean ratio 1.12 and 1.14 respectively).Conclusions: There is no difference between upper lower segment ratio in obese and normal children aged 7 to 10 years old. [AMJ.2016;3(1):147â51]Â DOI:Â 10.15850/amj.v3n1.721